The democratization of American Christianity - Hatch, Nathan O. (New Haven : Yale University Press, 1989)
"In this prize-winning book Nathan O. Hatch offers a provocative reassessment of religion and culture in the early days of the American republic, arguing that during this period American Christianity was democratized and common people became powerful actors on the religious scene. Hatch examines five distinct traditions or mass movements that emerged early in the nineteenth century£the Christian movement, Methodism, the Baptist movement, the black churches, and the Mormons£showing how all offered compelling visions of individual potential and collective aspiration to the unschooled and unsophisticated"--
I. Context -- 1. Introduction: Democracy and christianity -- 2. The crisis of authority in popular culture -- II. Mass movements -- 3. Storming heaven by the back door -- 4. Thundering legions -- III. Audience -- 5. The Sovereign audience -- 6. The right to think for oneself -- IV. Legacy -- 7. Upward aspiration and democratic dissent -- 8. Epilogue: The recurring populist impulse in American christianity -- Redefining the second great awakening : A note on the study of christianity in the early republic -- Appendix: A sampling of anticlerical and anti-calvinist christian verse -- Notes -- Index.
Includes bibliographical references (pages 244-303).
Print version record.
JSTOR
Keywords: United States -- Church history -- 19th century; Democracy -- Religious aspects -- Christianity -- History of doctrines -- 19th century; United States -- Church history -- 19th century; États-Unis -- Histoire religieuse -- 19e siècle.; 11.59 church history, history of doctrine: other; Democracy -- Religious aspects -- Christianity -- History of doctrines; United States; United States -- Church history; Christendom; 1800-1899; United States -- Christian church -- history; Church history